Teknik Metafora dalam Bimbingan Kelompok - Habsy, Bakhrudin All; Wandari, Nadya Indria; Zakirah, Amirah; Posopati, Anggita Nawangwulan (TSAQOFAH, 2024)
A metaphorical technique in counseling is a technique that facilitates the relationship between the student and the counselor through the creation of meaning indirectly. The aim of this research is to help counselors and counselor in understanding individuals meeting basic needs and achieving desired change. This research method uses library research by searching several sources such as journals, articles, books and other sources. It can be concluded that metaphor techniques in group guidance provide understanding, enhance the ability of students, as well as shape the character of students.